On Naturally Ordered Abundant Semigroups with an Adequate Monoid Transversal - Wei Chen (Discrete Dynamics in Nature and Society)
In this paper, we study a class of naturally ordered abundant semigroups with an adequate monoid transversal, namely, naturally ordered concordant semigroups with an adequate monoid transversal. After giving some properties of such semigroups, we obtain a structure theorem for naturally ordered concordant semigroups with an adequate monoid transversal.